(untitled) (Nigerian Journal of Technology, 2022)
A profound engineering design and modeling of fatigue strength machine for testing the failure which occurs when a metallic material is subjected to cyclic stresses is presented. The main goal is developing a locally made fatigue strength machine that can be used in material science laboratory. A major direction in this development of the machine is the ability to thread on the path of technology transfer and dominance by concentrating on the building of indigenous capacity. In carrying out the machine development, engineering design formulae were applied and Computer Aided Design modeling was developed. The developed fatigue strength testing machine had a designed machine capacity of 18875Nmm that sustained a motor power of 5.93kw. The machine shaft diameter determined to be 9.88mm developed an equivalent torque and bending moment of 45799.8Nmm and 40890Nmm respectively. The machine designed critical speed of 23.52rad/s had belt tensions on the tight and slack sides to be 139.02N and 44.65N respectively. The fabricated machine has the ability to record low and high fatigue cycles.